1993
DOI: 10.1159/000218287
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Subgroups: The Key Factor for Treatment Outcome in Metastatic Breast Cancer

Abstract: Background: Since prolongation of survival by chemotherapy has been questioned, palliation balanced with an acceptable quality of life is the primary aim in treating patients with metastatic breast cancer. Patients and Methods: 224 patients from 11 centers were randomized to treatment with 40 mg/m2 of Adriamycin or with 40 mg/m2 of epirubicin or with 12 mg/m2 of mitoxantrone each in combination with 600 mg/m2 of cyclophosphamide every 3 weeks. A special monitoring system including follow-up until death guarant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
1
5
0
1
Order By: Relevance
“…Median survival time after the occurrence of liver metastases is reported from 1 to 20 months [2,4,5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Median survival time after the occurrence of liver metastases is reported from 1 to 20 months [2,4,5,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It was believed that concomitant toxicity was 'worthwhile' in order to get a higher rate of CR which would result in longer median survival time. In an earlier performed prospective randomized study we had compared 3 combinations which differed moderately in their aggressiveness [1]. It has been shown that prognostic criteria were more important than the choice of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the entire population, neither remission rates nor median survival time differed significantly between the 2 groups receiving either mild monochemotherapy or aggressive combination chemotherapy. While subgroups eventually drawing benefit from combination treatment are being evaluated, we must state that quality of life and gain from treatment as measured in a modified Brunner's score [1,3] [18] showed a better CR rate with FEC 75 than with FEC 50 (p = 0.025) or with epirubicin (p = 0.002), but mean duration of response, TTP, and survival time were not different between the three groups. Only during the first 8 months, survival time seemed to be better in the FEC 75 group compared with the FEC 50 group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1984][1985][1986][1987][1988] hatte gezeigt, daß bei der Auswertung wichtige prognostische Faktoren zu berücksichtigen sind, da diese die Überlebenszeit deutlich beeinflussen [2]. Das Besondere an dieser größten prospektiv-randomisierten Datensammlung (n = 891, einschließlich von Low-risk-Fällen) für metastasiertes Mammakarzinom in Deutschland ist, daß einmal -im Gegensatz zu vielen anderen Studien -die Patientinnen so lange nachbeobachtet werden, daß solide Ergebnisse für den Überlebenszeitvergleich vorliegen, zum anderen aber auch von Anfang an Lebensqualitätserhebungen durchgeführt wurden.…”
Section: Tumorhistologieschlüssel (Ths) 1997unclassified